Pembuatan Website Profil Kelurahan Pager Agung sebagai Sarana Informasi Publik - Popi Dayurni; Rehan Surya Wijaya; Ahmad Altaf Hali; Ade Fricticarani; Ofan Sofian (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
The village website has an important role in providing transparent and accurate information to the public. Websites as a means of public information have proven effective in increasing citizen involvement in local government. Websites are also an effective means of conveying educational and informative information to the public. The creation of the Pager Agung Village profile website aims to increase the accessibility of public information, such as administrative services, current news, and community activities. Through this community service program, we design and implement a user-friendly and responsive website. The design of this system applies the System Development Life Cycle (SDLC) model. The results of this activity show an increase in citizen satisfaction with access to information and participation in village activities. In addition, this website has also increased the transparency of the village in managing public activities and funds.